2023
DOI: 10.7759/cureus.37702
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being of Adult Psoriasis Patients: A Narrative Review

Abstract: Psoriasis is a chronic systemic inflammatory condition, and psychiatric comorbidities are common in this condition. It is a non-communicable, autoimmune, and incurable disease. Psoriasis causes an adverse effect and is connected with various psychological symptoms like social isolation, guilt, and embarrassment of a patient. They decrease self-esteem because of depression, anxiety, stress, and substance abuse adults. The prevalence rate of adults is gradually increasing. This study uses various scales to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Psychological wellbeing has become a global concern, particularly in the context of chronic pathologies [1][2][3]. Chronic illnesses negatively impact the physical, mental, and social aspects of an individual's life, posing a clear stress factor that threatens their wellbeing [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological wellbeing has become a global concern, particularly in the context of chronic pathologies [1][2][3]. Chronic illnesses negatively impact the physical, mental, and social aspects of an individual's life, posing a clear stress factor that threatens their wellbeing [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a chronic inflammatory disorder with increased numbers of Th1, Th17, and Th22 cells, leading to the synthesis of interferon-γ, tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-22 (1). Psoriasis is found in 1-3% of the global population (2), with prevalences in adults differing between countries but ranging from 0.51% to 11.43% (3). A cross-sectional study found a psoriasis prevalence of 2,5% in Indonesia (4).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, depression, anxiety, stress, insomnia, and substance abuse have all been found to be higher in people with psoriasis compared with people without a skin condition. [1][2][3] Factors important to patients when discussing treatment options include overall symptom relief, rapid symptom relief, achieving and maintaining clear skin, effectiveness in 'high-impact' areas (such as the nails, scalp, palms, and soles), and the occurrence of side effects. 3 As psoriasis is a chronic disease, and loss of response is observed with some therapies over time, 4 studying long-term efficacy of new treatments is important.…”
Section: Introductionmentioning
confidence: 99%